Vertical heterostructures based on SnSe2/MoS2 for high performance photodetectors. (17th March 2017) - Zhou, Xing; Zhou, Nan; Li, Chao; Song, Hongyue; Zhang, Qi; Hu, Xiaozong; Gan, Lin; Li, Huiqiao; Lü, Jingtao; Luo, Jun; Xiong, Jie; Zhai, Tianyou
Abstract: Van der Waals heterostructures from atomically thin 2D materials have opened up new realms in modern semiconductor industry. Recently, 2D layered semiconductors such as MoS2 and SnSe2 have already demonstrated excellent electronic and optoelectronic properties due to their high electron mobility and unique band structures. Such combination of SnSe2 with MoS2 may provide a novel platform for the applications in electronics and optoelectronics. Thus, we constructed SnSe2 /MoS2 based van der Waals heterostructures using MoS2 as templates, which may enrich the family of 2D van der Waals heterostructures. We demonstrate that the vdW heterostructures with high symmetry crystallographic directions show efficient interlayer charge transfer due to the strong coupling. This strong coupling is confirmed by theory calculations, low-temperature photoluminescence (PL) spectra, and electrical transport properties. High performance photodetector based on the vdW heterostructure has been demonstrated with a high responsivity of up to 9.1  ×  10 3 A W −1 which is higher by two orders of magnitude than those MoS2 -only devices. The improved performance can be attributed to the efficient charge transfer from MoS2 to SnSe2 at the interface.